Influence of Compensation and Rewards on Employee Performance and Employee Innovative Behaviour: A Mediating Role of Organisational Climate - Sriwan, Piyaon; Jermsittiparsert , Kittisak (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The purpose of the study is concerned with determining the mediating effect of organisational climate in the relationship between compensation/ rewards & employee performance and with compensation/ rewards and employee innovative behaviour. Design/ Method: The study has adopted a quantitative approach based on the survey conducted from 381 SMEs operating in Indonesia. The study has utilised SEM technique as the statistical analysis technique and performed the confirmatory factor analysis along with path analysis to determine the mediation effect. Findings: The findings of this study suggests a partial mediating effect of organisational climate existed in the relationship between compensation/ rewards & employee performance and with compensation/ rewards & employee innovative behaviour. Limitations: The study is purely based on the SME sector of Indonesia. With this regard, the study has limitations while applying the findings of this research to other sized companies and companies of different geographical locations.